Capturing the impact of adolescent inpatient admissions: The Social Connectedness Scale. (July 2019) - Phillips, Katy; Lawler Whatson, Bridie; Wells, Emma; Milson, Gordon; Hartley, Samantha
Background: Outcome measurement is central to health service provision. In child and adolescent mental health services (CAMHS), there are established tools used to assess symptoms and track progress. However, there is a relative dearth of assessments of subjective well-being or recovery. Social connectedness is a concept linked with well-being and risk in young people. We sought to evaluate the utility and acceptability of a measure of social connectedness in inpatient CAMHS. Method: As part of routine clinical practice, we asked 92 young people (mean age 16 years old) on two inpatient CAMHS wards to complete the Social Connectedness Scale, alongside other assessments, and also comment on its acceptability. We repeated the measure on discharge from the unit. Results: The findings showed that the measure was internally consistent (α = .910) and sensitive to change in this population. Scores also correlated with another self-report measure focusing on well-being and mental distress, but not with clinician-rated measures. Ratings of relevance and ease of understanding were reasonable and young people value social connection. Conclusion: The Social Connectedness Scale might offer an appropriate method of exploring this element of young peoples' experience and progress, as part of inpatient mental health admissions.